Entrepreneurs' imprint: Survival and sustainable development of private aesthetic plastic surgery hospitals in China - Li Xu; Ming-xia Liu; Hao Yao (Journal of Global Entrepreneurship Research, 2019)
Recently, the private aesthetic plastic surgery industry in China is developing rapidly and has become the fourth largest service industry of the country which contributes to 1.2% portion of the national~GDP and helps to improve employment. Thus, the sustainable development of the industry plays an important role in the sustainability of the Chinese economy which is a problem that cannot be ignored. From the perspective of organizational imprinting, this paper selects seven newly established private aesthetic plastic surgery hospitals in central China as research samples and applies semi-structured interview and content analysis to investigate the relationship between personal characteristics of entrepreneurs and survival trajectories of these hospitals. Results show that entrepreneurs' imprint takes effect in the course of establishing a new hospital through entrepreneurial motivation and initial strategy. Specifically, entrepreneurs' age, educational background, geographical identity and industry experience all contribute to the entrepreneurial success. In addition, entrepreneurs' imprint may be effective in the initial and early stage and then fades away with environmental changes. Corporate strategy is a useful complement to entrepreneurs' imprint afterwards.
Keywords: 650; Entrepreneurs' imprint; Aesthetic plastic surgery hospital; Sustainable development; Entrepreneurial motivation; Initial strategy